1989
DOI: 10.1525/aa.1989.91.1.02a00050
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Basis for Shipibo Soil Classification and Land Use: Changes in Soil‐Plant Associations with Cash Cropping

Abstract: Since the Shipibo began cash cropping rice, their land use patterns have changed with proportionately less utilization of soft sandy soils, which are best for staple Musa production, and greater use of harder clayey soils, which are more suitable for rice and root crops. Statistical analysis of soil samples reveals the physical‐chemical basis for Shipibo soil categories and indicates the effect ofswidden agriculture on levels of important soil characteristics. While cultural principles for planting have summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…However, one of the youngest interviewees could not answer any question related to traditional agricultural knowledge. Similarly, Behrens (1989) observed that Shipibo communities increasingly ignored traditional agricultural knowledge when they began cash cropping rice. Concern over the lack of intergenerational knowledge transfer was also emphasized in the historical timeline focus group, previous Panaillo fieldwork (Hofmeijer et al, 2012), institutional interviews (n=6), and interviews with Panaillo residents (n=4).…”
Section: Assimilation Social Modelmentioning
confidence: 99%
“…However, one of the youngest interviewees could not answer any question related to traditional agricultural knowledge. Similarly, Behrens (1989) observed that Shipibo communities increasingly ignored traditional agricultural knowledge when they began cash cropping rice. Concern over the lack of intergenerational knowledge transfer was also emphasized in the historical timeline focus group, previous Panaillo fieldwork (Hofmeijer et al, 2012), institutional interviews (n=6), and interviews with Panaillo residents (n=4).…”
Section: Assimilation Social Modelmentioning
confidence: 99%
“…Traditional populations have long been recognized to have a highly accurate knowledge for selecting soils and lands for different uses depending on existing vegetation and other ecological site characteristics (Behrens, 1989;Moran, 1974). In contrast, newly arrived colonists lack this knowledge, but acquire it through trial and error and social networks.…”
Section: Tree Plantingmentioning
confidence: 99%
“…This community consists of 31 families, among which there are members of different ethnic groups belonging to the Pano family, who arrived from different communities located in the lower part of the Ucayali River. The Shipibo-Conibo have been fairly well-studied in the past (Behrens 1989, Follér 1995, Hern 1992, Martin 1982, Tournon & Reategui 1983, Tschopik 1958. They inhabited the Ucayali region long before the city of Pucallpa was built, and the vast majority possess bilingual skills (Tournon 2002).…”
Section: Methodsmentioning
confidence: 99%